Optimization method of multi-parameter coupling for a hydraulic rolling reshaper based on factorial design - Li, Hongfei (Strojniški vestnik, 2023)
A hydraulic rolling reshaper is an advanced shaping technology with superior protection for casings, and the structural parameters of the reshaper affect its shaping effect on deformed casing directly. To improve the shaping capacity of the reshaper, a multi-parameter coupling optimization method of hydraulic rolling reshaper is proposed to optimize the design of the factors with significant influence under the premise of screening multi-structural parameters. In this paper, according to the working principle of the reshaper, considering the contact nonlinearity between the hydraulic rolling reshaper and deformed casing, as well as the material nonlinearity of the casing, a parametric finite element model of the hydraulic rolling reshaper repairing the shrinkage deformation of casings was developed. The remarkable factors were screened by factorial design, the sample points were generated by optimal Latin hyper-cube design (OLHD), and the response surface models were established by stepwise regression. Therefore, with the maximum plastic deformation of casings as the objective function, the maximum equivalent stress, residual stress, and the plastic deformation of casings as the constrained conditions, an optimized mathematical model for a reshaper was constructed, and the genetic algorithm (GA) is performed to obtain the optimal combination of parameters. The results showed that the optimal reshaper made the shaping process safe and effective, the plastic deformation of casings after single shaping was increased by 11.38 %, and the shaping effect was better (96.48 %), which can effectively improve the safety performance and shaping ability of the reshaper.
Keywords: factorial design; faktorska zasnova; hidravlična valjalna oblikovalna naprava; hydraulic rolling reshaper; metoda odzivnih površin; obnova vrtin; optimizacija konstrukcije; orthogonal test; ortogonalni test; structural optimization